CASE STUDY: DEVELOPING TANZANIA’S TRANSPORT INFRASTRUCTURE MANAGEMENT SYSTEM (TIMS) - Glenn ROBINSON (Journal of Construction Project Management and Innovation)
This case study profiles the steps taken to develop a process for developing a transportation information management system protype. The case study was initiated in response to a pattern of growth whereas, Tanzania is increasingly becoming a mobile society that suffers severely from traffic congestion, delay and mobile source pollution. Meeting the challenges of greater mobility, accessibility, land use development, economic growth and revenue constraints requires that transport investment and maintenance strategies be optimized. In this case study we define transportation information management system (TIMS), in the context of the Tanzania 2014 transportation network. In doing so an argument is made for developing a base line digital transport network analysis, as a starting point. In doing so, we identify a suite of decision-making tools and a stable of performance variables. As well, this case study presents a draft: work plan which emerged during this effort.